ANALYSIS OF THE PROBLEM OF OPTIMAL CONTROL OF THE ENERGY CONVERSION PROCESS IN A TURBO UNIT - Tsyganash, V. E.; Zverev, M. V.; Beloivanenko, Y. S. (Radio Electronics, Computer Science, Control, 2024)
Technological aspects and problems of manufacture of the electric power on thermal power main lines are considered. The concept of optimum control by energy transformation process in a turbine unit is stated.